Primates face to face conservation implications of human and nonhuman primate interconnections - Fuentes, Agustín 1966-; Wolfe, Linda D. 1942- (Cambridge studies in biological and evolutionary anthropology, 2002)
As our closest evolutionary relatives, nonhuman primates are integral elements in our mythologies, diets and scientific paradigms, yet most species now face an uncertain future through exploitation for the pet and bushmeat trades as well as progressive habitat loss. New information about disease transmission, dietary and economic linkage, and the continuing international focus on conservation and primate research have created a surge of interest in primates, and focus on the diverse interaction of human and nonhuman primates has become an important component in primatological and ethnographic studies. By examining the diverse and fascinating range of relationships between humans and other primates, and how this plays a critical role in conservation practice and programs, Primates Face to Face disseminates the information gained from the anthropological study of nonhuman primates to the wider academic and non-academic world